Visualizing Knowledge: Enhancing ESP Students’ Learning through Digital Poster-Based Collaborative Learning - Wulandari, Fitriya Dessi; Yuliani, Fitria; Rifai, Dian Muhammad; Rizkiyah, Faiqotur; Nugroho, Arif; Aminudin, Muhammad Fauzan (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Vocabulary The integration of technical knowledge and oral communication remains a persistent challenge in English for Specific Purposes (ESP) classrooms, particularly in health-related disciplines where students are required to master complex subject matter while communicating it effectively in English. This study investigates the effectiveness of a digital poster-based collaborative learning model in enhancing both technical comprehension and oral communication skills among first-semester Speech Therapy students. The study aimed to examine how an integrated pedagogical approach combining digital tools, collaborative learning, and multimodal strategies influences students’ learning outcomes in an ESP context. A Classroom Action Research design consisting of two cycles was implemented with 138 students in a health polytechnic institution. Data were collected through pre-test and post-test assessments, oral presentation rubrics, classroom observations, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics and paired-samples t-tests, while qualitative data were analyzed thematically. Findings showed a significant improvement in students’ performance, t (137) = −47.88, p < .001, with post-test scores (M = 78.57, SD = 6.08) exceeding pre-test scores (M = 50.80, SD = 7.23). Qualitative results indicated increased engagement, improved conceptual understanding, and greater communicative confidence. Digital posters supported information synthesis, while collaboration facilitated peer scaffolding and reduced speaking anxiety. Multimodal learning enhanced cognitive processing through the integration of visual, written, and oral modes. The study concludes that digital poster-based collaborative learning effectively improves technical and communicative competencies in ESP settings and offers a practical framework for integrating digital literacy, collaboration, and multimodal pedagogy in health education.